(untitled) (Lex localis - Journal of Local Self-Government, 2024)
This article examines administrative authority in higher education using Guangdong, Beijing, Guangxi, and data from other regions. It examines whether higher education’s administrative management system, personnel quality, assessment standards, and public attention can generate administrative power at the institutional, university, and social levels. The study aims to determine if the system, staff quality, and public involvement are the major variables in building administrative authority. The study used data from Guangdong, Beijing, Guangxi, and other regions, employing empirical analysis to evaluate the impact of the administrative management system, personnel quality, and public attention on administrative power. Results reveal that the management system, personnel quality, and evaluation criteria contribute to building administrative authority. The quality of personnel and system is the most important, and assessment criteria are secondary. Public engagement can build administrative authority, but it’s hard to implement and enforce. Improving administrative personnel quality and management systems is crucial for building effective administrative authority in higher education, though public engagement remains challenging to implement.